Collaborative and Inclusive Journalism: More Than Words. (March 2020) - Ford, Rochelle; Gonzales, Sara; Quade, Victoria
The failure of the news media to include diverse voices is a global issue. Journalism students and novice journalists need to be trained how to report on marginalized communities. However, this training necessitates journalism educators to both recognize why these attempts have failed in the past and be proactive in identifying ways in which journalism programs can be truly inclusive and collaborative.